Transparency in DADOS: submissions, reviewers, and editorial workflow diversity in recent years - Luiz Augusto Campos; Candido, Marcia. (Dados: Revista de Ciências Sociais, 2022)
This editorial discusses general data concerning the manuscripts workflow of DADOS, and the challenges faced by the journal in the last few years. It presents a scientometric analysis of several dimensions of the periodical’s workflow, ranging from submissions to the profile of reviews and reviewers also addressing persisting gender and spatial inequalities and the journal’s different impact metrics. The work aims to ensure greater transparency in editorial processes without losing sight of the discretion criteria that underly our anonymous peer-review system. Besides, our goal is to share the strategies employed to overcome obstacles faced by science communication in Brazil in the hope that they may work as instruments of resistance against the many and recurring crises faced by other national and international scientific journals.